Implementasi Prinsip Manajemen Kesiswaan dalam Mengembangkan Potensi Belajar Siswa - Muh. Bachtiar Aziz (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2021)
This study discusses the implementation of student management principles in developing student learning potential at SMA Negeri 12 Bone. This study aims to determine the principles of student management in developing student learning potential. The method used by researchers is field research (field research) by conducting observations, interviews, and documentation. The data obtained were processed using qualitative methods to describe research on the Implementation of Student Management Principles in Developing Student Learning Potential at SMA Negeri 12 Bone, kec. Sibulue Kab. Bone. In analyzing the data, the author uses data reduction, data display, conclusion drawing/verification. The results showed that first, a). Students are made as subjects, not objects. With a modern teaching system that places students as active parties in forming their own knowledge. Second, b). The various circumstances and conditions of students that at SMAN 12 BONE Kec. Sibulue if in carrying out the learning process there are students who have problems with their learning, then the student will be given gentle advice so that he does not feel blamed. Third, c). at SMAN 12 BONE Kec. Sibulue has many ways to increase student learning motivation, by conducting regular evaluations to find out the extent to which student learning has improved. Fourth, d). cognitive domain abilities include applying, analyzing, and assessing relevant learning experiences. in the affective domain, the competencies to be achieved include, among others, the levels of responding, appreciating, and valuing. While the psychomotor domain, the competencies achieved include the level of initial movement, semi-routine, routine movements to achieve these competencies, learning experiences that need to be carried out. Student learning potential at SMAN 12 BONE Kec. Sibulue, First, to overcome students who have weak health conditions can be done by giving these students special attention, inviting them to participate and forming study groups with other students. Second, Psychological Potential at SMAN 12 BONE Kec. Sibulue method is used to improve the mental and intellectual abilities of students by flexible and continuous learning by adding new insights.